A quantitative study on the synergistic effect between limestone powder and supplementary cementitious materials. Issue 7 (28th July 2022) - Wang, Dehui; Jia, Huangfei
Abstract : As an industrial solid waste from limestone quarrying, limestone powder (LP) is often used in cement-based materials to reduce cost and carbon dioxide emissions. It is well known that the synergistic effect between LP and alumina-rich supplementary cementitious materials (SCMs) influences the properties of cement-based materials. To study the synergistic effect quantitatively, the hydration heat, hydration products and porosity of cement pastes with different binders were investigated. Test results showed that the synergistic effect between LP and fly ash (FA) or slag (S) improved the hydration degree and increased the total hydration heat of the pastes. When FA or S were incorporated along with LP, the calcium carbonate consumption at 3 days increased from 2.0 wt% to 4 wt%; at 180 days it increased from 2.4 wt% to 9.3 wt% (with FA) and 11.8 wt% (with S). The incorporation of FA or S also increased the diffraction peak of carboaluminate, indicating more carboaluminate was formed. The synergistic effect between LP and SCMs refined the pore structure and reduced the porosity of the cement pastes. The synergistic effect between LP and FA or S increased the density of the cement pastes by 1.04% or 1.41%, respectively, and correspondingly improved the compressive strength of the pastes.